2020
DOI: 10.1108/jhti-06-2020-0108
|View full text |Cite
|
Sign up to set email alerts
|

Cross-nationality importance performance analysis of Middle East all-inclusive mass tourism destination image

Abstract: PurposeThe paper aims to analyze cognitive attributes affecting the overall destination image perception of British, German and Russian tourists toward Antalya, a well-positioned mass tourism destination in the East Mediterranean region dominated by an all-inclusive (AI) system.Design/methodology/approachThe paper is an empirical study using a structured questionnaire conducted in the summer of 2018 with 274 British, 179 German and 231 Russian tourists departing to their respective source markets from Antalya … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Although the resulting analysis of path coefficients and their significance levels can explain the relationships among the examined variables, such approach technically precludes prioritizing constructs and indicators to improve a certain target variable. Methodologically, this study contributes to the travel and tourism technology area (Ceylan et al , 2021), where IPMA with GSCA approach was utilized to prioritize app content attributes. Pragmatically, the prioritization of travel app components provides a foundation for travel service providers and app designers to improve necessary dimensions in ensuring favorable tourists' app usage intention.…”
Section: Discussionmentioning
confidence: 99%
“…Although the resulting analysis of path coefficients and their significance levels can explain the relationships among the examined variables, such approach technically precludes prioritizing constructs and indicators to improve a certain target variable. Methodologically, this study contributes to the travel and tourism technology area (Ceylan et al , 2021), where IPMA with GSCA approach was utilized to prioritize app content attributes. Pragmatically, the prioritization of travel app components provides a foundation for travel service providers and app designers to improve necessary dimensions in ensuring favorable tourists' app usage intention.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of a study carried out in Israel indicated that affective image had a higher positive impact on overall destination image and future behavior than did cognitive image (Stylidis et al , 2017). Ceylan et al 's (2021) research showed that each nationality had a different perception of Antalya, one of the most popular destinations in Turkey, though British, German and Russian tourists perceived the city as an all-inclusive mass tourism destination.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Tourist destination image has attracted researchers since 1970 (Chen et al, 2014). Gunn in 1992 started conducting a research (Viet et al, 2020) on how a destination can attract potential tourists (Saini & Arasanmi, 2020) because destination image affects or influences tourist behaviors (Jenkins, 1999;Erawan, 2019;Ceylan et al, 2020;Afshardoost & Eshaghi, 2020). The term tourist destination image has unclear definition (Echtner & Ritchie, 1993;Jenkins, 1999;Loi et al, 2017;Al-Gasawneh & Al-Adamat, 2020;Viet et al, 2020), which represents individual mentality on their understanding, belief, feeling, and total perception of a tourist destination (Baloglu & McCleary, 1999;Crompton, 1979).…”
Section: Tourist Destination Imagementioning
confidence: 99%
“…Image is an accumulation of beliefs, ideas, impressions that a person has on a tourist destination from time to time (Crompton, 1979;Baloglu & Gartner, 1994;McCleary, 1999;Leisen, 2001). Since the nature of a tourist image formation is always dynamic (Ghazali & Cai, 2013) which comes from cognitive, affective, and conative elements (Afshardoost & Eshaghi, 2020;Ceylan et al, 2020;Herle, 2018). When a factor that forms an image changes, but the change does not affect an image, whether it is positive and negative changes (Fakeye & Crompton, 1991).…”
Section: Tourist Destination Image and Tourist Behavioural Intentionmentioning
confidence: 99%
See 1 more Smart Citation